The Comprehensive Study of Cultural Aspects in The Translation of Batak Folklore “Boru Saroding” - Simanjuntak, Hotnida Irawaty; Lubis, Syahron; Setia, Eddy; Mono, Umar (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Translation of folklore involves not only transferring language from one form to another but also conveying the cultural values embedded in the original narrative. One of the most culturally significant elements in traditional stories is kinship terminology. This study examines the translation of kinship terms in the Batak folklore Boru Saroding and explores how their cultural meanings are preserved or modified in the translation process. The research aims to identify the types of kinship terms appearing in the folklore and analyse the strategies used to translate them into English. This study uses a qualitative descriptive method with a cultural translation approach. The data consist of kinship terms found in the Batak folklore Boru Saroding and their English equivalents. The data were collected through document analysis and examined using frameworks of cultural equivalence and translation strategies. The findings show that Batak kinship terms represent complex social relationships that do not always have direct equivalents in English. As a result, translators employ several strategies, including borrowing, descriptive translation, and cultural substitution, in order to convey the intended meaning. Among these strategies, borrowing appears most frequently because many Batak kinship concepts reflect unique cultural and social structures. This study highlights the importance of maintaining kinship terminology to preserve the cultural authenticity of folklore translations. Therefore, translators must carefully balance readability for the target audience with accurate cultural representation when translating traditional narratives.